2019
DOI: 10.1002/fedr.201800024
|View full text |Cite
|
Sign up to set email alerts
|

A morphometric study of the restinga ecotype of Anacardium occidentale (Anacardiaceae): wild coastal cashew populations from Piauí, Northeast Brazil

Abstract: The infraspecific taxonomy of wild Anacardium occidentale is little studied. We investigated whether wild populations on coastal dunes in Piauí, Brazil differed from non‐wild populations. Ten populations were sampled and twenty one morphological variables were measured. Variation within and between populations was investigated with univariate and multivariate statistics. Dune populations were mostly more similar to one another than to domesticated ones. There was significant correlation between inter‐populatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 40 publications
0
12
1
Order By: Relevance
“…Initially, A. othonianum was treated as a synonym for the commercial cashew, A. occidentale 8 . Studies targeting the diversity of natural field populations like agronomic and plant breeding studies, such as Gomes et al 9 and Andrade et al, 10 have nevertheless recognized A. othonianum as a distinct species, essentially a wild Cerrado form. In general, the wild fruits of Anacardium ssp.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, A. othonianum was treated as a synonym for the commercial cashew, A. occidentale 8 . Studies targeting the diversity of natural field populations like agronomic and plant breeding studies, such as Gomes et al 9 and Andrade et al, 10 have nevertheless recognized A. othonianum as a distinct species, essentially a wild Cerrado form. In general, the wild fruits of Anacardium ssp.…”
Section: Introductionmentioning
confidence: 99%
“…These germplasm collections have been the basis of many studies that aimed to compare the genetic diversity of cashew accessions from different regions. Some used morphological markers (see references in Andrade et al 2019;Bionoset 2019), but genotyping with molecular markers such as isozymes, RAPDs, ISSRs, AFLP, microsatellites and ITS sequence data is now more usual, sometimes in combination with morphological descriptors; these studies have been carried out predominantly on material from India (e.g. Dhanaraj et al 2002;Rout et al 2002;Samal et al 2002;Archak et al 2003a, b;Samal et al 2003;Desai 2008;Archak et al 2009;Thimmappaiah et al 2009;Dashmohapatra et al 2014;Sethi 2015;Jena et al 2016), Brazil (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that in Asia and Africa cashews have a relatively narrow genetic base (Aliyu 2012;Archak et al 2009) and diversity within the natural South American range of the species would be expected to be greatest. However, the genetic and phenotypic variability of natural populations in Brazil remains poorly known as there are few such studies (Andrade et al 2019). Biosystematic investigations of A. occidentale have been hampered by difficulties in determining its species limits and the status of populations as natural, naturalised or domesticated (Johnson 1972(Johnson , 1973Mitchell and Mori 1987).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations